The Birth of Legal Radiological Sciences in Brazil (Research, Society and Development, 2022)
The present work contemplates the objective of developing an exploratory study with a qualitative approach, aiming to include professionals of radiological techniques in state or federal public notices as specialists in Legal Radiology. Therefore, an exploratory literature review was carried out using the PubMed database. The reflections, so far, allow for the following inferences: a) the fields subject to expertise have their limits in the joint reading between Law No. 7394 / 85 and Resolution No. 2/2012 - CONTER; b) the absence of trained professionals in the area migrated the demands of specialists to related areas, given the application of different methodologies in the analysis of the same objects; c) the need to create a technical and standardized framework for the training and specialization of technicians and technologists in medical radiology in the field of Legal Radiological Sciences. However, the emergence of scientific works problematizing and systematizing expert attributions will open up new work opportunities and sub-branches of expert activity in radiology.